2002
DOI: 10.1177/073401680202700106
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Assault of College Women: A Feminist Interpretation of a Routine Activities Analysis

Abstract: Sexual assault has been a frequent topic of research for several decades, especially for feminist researchers. Generally, feminist research suggest that there are high levels of sexual assault against women because of a patriarchal, rape-supportive culture. However, not all women have the same heightened risk for sexual assault victimization. Wh the feminist perspective does not adequately account for are the variations in rape victimization rates across the female population. This is where the importance of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
191
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(201 citation statements)
references
References 69 publications
9
191
0
1
Order By: Relevance
“…Looking more specifically at the notion of suitable targets, the routine activities approach also assumes that criminal victimization is not randomly distributed in society and that actual crime-commission is a function of the convergence of lifestyles and criminal opportunity. Hence, daily activities and lifestyles nurture a criminal opportunity structure by enhancing the exposure and proximity of crime targets to motivated offenders (Felson & Cohen, 1980;Miethe & Meier, 1990;Mustaine & Tewksbury, 2002). When looking at victimization, studies have shown that it is the activities and lifestyles of individuals that carry them through contexts and interactions that will, in return, modify their likelihood of being victimized (Miethe & Meier, 1990;Mustaine & Tewksbury, 2002;Tewksbury & Mustaine, 2003).…”
Section: Victims' Routine Activities and Target Selection Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Looking more specifically at the notion of suitable targets, the routine activities approach also assumes that criminal victimization is not randomly distributed in society and that actual crime-commission is a function of the convergence of lifestyles and criminal opportunity. Hence, daily activities and lifestyles nurture a criminal opportunity structure by enhancing the exposure and proximity of crime targets to motivated offenders (Felson & Cohen, 1980;Miethe & Meier, 1990;Mustaine & Tewksbury, 2002). When looking at victimization, studies have shown that it is the activities and lifestyles of individuals that carry them through contexts and interactions that will, in return, modify their likelihood of being victimized (Miethe & Meier, 1990;Mustaine & Tewksbury, 2002;Tewksbury & Mustaine, 2003).…”
Section: Victims' Routine Activities and Target Selection Processmentioning
confidence: 99%
“…As proposed by Kaufman et al (2006), "opportunities are most directly influenced by the victim's situation (e.g., walking alone), target location (e.g., parks), and the involvement of facilitators" (p. 112). For example, studies have consistently shown that engaging in social activities away from home or spending a good proportion of time in places where strangers aggregate is associated with an increased risk of criminal victimization (Mustaine & Tewksbury, 2002;Tewksbury & Mustaine, 2003). Offenders are likely to decide on a suitable area in which to offend, based on the likelihood of finding suitable targets, the latter being a function of the number of potential targets in one location (Bernasco & Nieuwbeerta, 2005).…”
Section: Victims' Routine Activities and Target Selection Processmentioning
confidence: 99%
“…-and aware of), as well as the distribution of targets (Beauregard, Proulx, & Rossmo, 2005;Clarke & Felson, 1993;Deslauriers-Varin & Beauregard, 2010;Eck & Weisburd, 1995). Indeed, daily activities and lifestyles will nurture a criminal opportunity structure by enhancing the exposure and proximity of crime targets to motivated offenders (i.e., crime concentration) (Felson & Cohen, 1980;Miethe & Meier, 1990;Mustaine & Tewksbury, 2002).…”
Section: Crime Patternmentioning
confidence: 99%
“…Students' lifestyle and routine activities have been extensively examined as the correlates of campus crime in previous literature. These studies have revealed that students' characteristics and lifestyles, such as their relationship behaviors and alcohol drinking habits, are important determinants of their victimization (Siegel & Raymond, 1992;Wolkvein et al, 1995;Fisher et al, 1998;Henson & Stone, 1999;Mustaine & Tewksbury, 2002;Sloan et al, 2000;Dowdall, 2013;Mustaine & Tewksbury, 2013). …”
Section: Campus Crime and Safetymentioning
confidence: 99%
“…(1) Much of the extant research on campus safety are either descriptive studies, providing estimations of campus crime (Fisher, Cullen, & Turner, 2000;Kilpatrick, Resnick, Ruggiero, Conoscenti, & McCauley, 2007;Stewart & Fisher, 2013;Belknap & Erez, 2013) or explanatory research examining the factors that contribute to campus crime occurrence (Siegel & Raymond, 1992;Fisher & Nasar, 1992;Nasar & Fisher, 1993;Wolkvein, Szelest & Lizotte, 1995;Fisher, Sloan, Cullen & Lu, 1998;Henson & Stone, 1999;Mustaine & Tewksbury, 2002;Sloan, Lanier, & Beer, 2000;Dowdall, 2013;Mustaine & Tewksbury, 2013). The existing body of research is lacking an evaluation perspective focusing on the effectiveness of policies and programs designed for campus safety.…”
Section: Significance Of the Studymentioning
confidence: 99%